PENGARUH KEADILAN, SELF ASSESSMENT SYSTEM, TEKNOLOGI DAN INFORMASI PERPAJAKAN, PEMAHAMAN PERPAJAKAN DAN PELAYANAN APARAT PAJAK TERHADAP TINDAKAN TAX EVASION: Studi Kasus pada Wajib Pajak Orang Pribadi di Kantor Pelayanan Pajak Pratama Denpasar Barat - Ni Putu Aris Radithiya Dewi; Made Yudi Darmita (Journal Research of Accounting, 2022)
This research aims to examine the effect of justice, self-assessment system, technology and taxation information, understanding of taxation and service of tax officers on tax evasion. The population in this research were individual taxpayers at the West Denpasar KPP Pratama registered in 2020, amounting to 139,011 people. The sampling method used is the accidental sampling method, while the data collection is done by survey method through questionnaire technique. The number of samples in this study was 100 respondents. The results of this research questionnaire were measured using a Likert scale. The data analysis technique used is multiple linear regression analysis technique. The results of this research indicate that the significant level of each independent variable which is smaller than 0.05 means that justice, self-assessment system, technology and taxation information, understanding of taxation and service of tax officers have a negative effect on individual taxpayers' taxes evasion measures in the KPP. West Denpasar Primary.